Occurrence, Source, and Mobilization of Iron, Manganese, and Arsenic Pollution in Shallow Aquifer - Md. Shajedul Islam; M. G. Mostafa (Geofluids)
This investigation is aimed at exploring the mobilization and sources of Fe, Mn, and As in aquifers through geochemical characterization, spatial analysis, and statistical approaches. Analytical results showed that the average concentrations of Fe (10.17 mg/L) and Mn (3.6 mg/L) crossed the guideline value but not As in all samples. In this study, the elevated levels of dissolved organic carbon, salinity, total hardness, and log10 pCO2; the lower value of dissolved oxygen; and some oxidizing groups of samples influence the reductive environment of Fe and Mn weathering. The investigation illustrated that the source of both metals on the upper platform is consolidated silty soil and aquifer sediment, whereas, in the river valley, they originate from Fe and Mn-bearing nodules in the rich clay layer and tidal mud. In addition, the frequent fluctuation of river flow, excess water mining, and an unbalanced recharge/discharge ratio are the causes of higher concentrations of both metals. The correlation matrix and factor analysis of Fe and Mn with redox-sensitive water variables confirmed that a favourable reductive situation fosters the Fe and Mn release process. Studies have also shown the significant possibility of forming a metal complex with organic and inorganic substances. The higher dissolution of Fe and Mn minerals causes As to be adsorbed on them, leading to less release of As into groundwater. This investigation provides a basis for the rational use of groundwater and the defense of public health in zones with high Fe and Mn contents.